Improved water saturation estimation in shaly sandstone through variable cementation factor - Wan Bakar, W.Z. (Springer Science and Business Media Deutschland GmbH, 2021)
Estimation of water saturation, Sw, in shaly sandstone is an intricate process. The surface conduction of clay minerals adds up to the electrolyte conduction in the pore spaces, thus generating high formation conductivity that overshadows the hydrocarbon effect. In each resistivity-based water saturation model, the key parameter is formation factor, F, which is typically derived from Archieâs Law. Referring to a logâlog plot between formation factor and porosity, cementation factor reflects the slope of the straight line abiding Archieâs Law. In the case of shaly sandstone, derivation based on Archieâs Law in combination with WaxmanâSmits equation leads to higher cementation factor, m*. In the shaly parts of the reservoir, high m* is counterbalanced by clay conductivity. Nonetheless, high m* used in clean parts increases Sw estimation. In this study, the variable cementation factor equation is introduced into the standard correlation of Sw versus Resistivity Index, RI, to develop a water saturation model with shaly sandstone parameters. Data retrieved from two fields that yielded mean arctangent absolute percentage error (MAAPE) were analysed to determine the difference between calculated and measured data within the 0.01â0.15 range for variable cementation factor method. The conventional method yielded maximum MAAPE at 0.46. Â© 2021, The Author(s).